EFEKTIVITAS KONSUMSI VIRGIN COCONUT OIL dan SUSU KEDELAI TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS - Wahyuni, Iin; Utaminingtyas, Farida; Apreliasari, Helmy; Xanda, Adhesty Novita; Aditia, Dita Selvia; Destri, Yuhelva; Muri, Putri Hilwati (Universitas Aufa Royhan, 2023)
Providing breast milk (ASI) to babies aged 0-1 years has very important meaning, especially regarding meeting the needs for nutrients and other substances that form the body's immunity against disease. Exclusive breastfeeding at the age of 0-6 months is considered very strategic, because at that age the baby's condition is still very unstable and susceptible to various diseases. The coverage of babies < 6 months old receiving exclusive breastfeeding in Lampung Province in 2022 is 75.37%, where this figure has reached the expected target of 70% (Lampung Province Health Profile, 2022). The aim of the research is to analyze the effect of giving soy milk and VCO (Virgin Coconut Oil) on increasing breast milk production for postpartum mothers. This research method is quasi-experimental with a one group pre and post test design approach. The results of the research are that there is a difference in the increase in breast milk production of postpartum mothers who consume soy milk and VCO (virgin coconut oil) at the Archa Medica clinic in South Tangerang City with a Sig value. (2-tailed)/ p= 0.004. Conclusion: VCO and soy milk are proven to increase breast milk production. Suggestions: Providing information and knowledge to postpartum mothers regarding the benefits of soy milk and VCO to utilize natural ingredients available in the community for consumption to facilitate breast milk